Reading, Reporting, and Remembering: A Case Study of the Maryknoll Sisters' Diaries - Yakel, Elizabeth (Archivaria, 2004)
This paper presents a case study of the record-keeping practices surrounding the diary within the context of one religious community: the Maryknoll Sisters. Diary writing began in 1912 and essentially ended in 1967 after reforms were instituted in response to Vatican II. The article traces: (1) the context and history of diaries; (2) outlines the evolution of the warrant and recordkeeping practices surrounding diaries; (3) discusses the varied purposes to which diaries were put; and (4) examines the reasons for the discontinuation of the diaries within the context of this religious community. The analysis demonstrates how the record-keeping traditions and the Maryknoll Sisters' culture redefined the diary genre to fit their particular needs. By doing this, the diaries were versatile records used both within the context of the community and as a means of engaging broader audiences. In the process, the diaries supported community identity, helped to maintain control over far-flung missioners, and shaped the image of the sisters for external readers. RÉSUMÉ Cet article présente une étude de cas des pratiques de gestion des documents entourant un journal dans le contexte d'une communauté religieuse particulière: les Maryknoll Sisters. La rédaction de ce journal a débuté en 1912 et s'est terminée en 1967 après que des réformes furent apportées en réponse à Vatican II. Cet article présente les quatre volets suivants: (1) le contexte et l'historique des journaux (ou annales); (2) l'évolution des pratiques de gestion des documents qui ont entouré ces journaux; (3) les différentes raisons de rédiger des journaux, et (4) pourquoi les communautés religieuses ont cessé de tenir de tels journaux. L'analyse de l'auteure montre comment les traditions de gestion des documents, ainsi que la culture des Maryknoll Sisters, ont redéfini le genre littéraire du journal afin de l'adapter à leurs propres besoins. Par le fait même, les journaux sont devenus des documents utilisés à la fois pour les besoins internes de la communauté et ont servi à impliquer un auditoire beaucoup plus vaste. Les journaux ont ainsi renforcé l'identité de la communauté, aidé à maintenir le contrôle sur les missionnaires éloignées et façonné l'image des sœurs pour les lecteurs externes.